Prevalence and Association of Helicobacter Pylori Infection in Bowel Disease at Dr. Cipto Mangunkusumo General National Hospital 2010–2021 - Simadibrata, Marcellus; Mustikarani, Dewi (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2023)
BSTRACT[WU1] [DM2] Background: Recent studies showed contrasting associations between Helicobacter pylori infection and organic bowel disorders, where positive associations were reported in colorectal carcinoma (CRC) and colorectal polyp, while a protective association was observed in patients with inflammatory bowel diseases (IBD). We aim to determine the association between H. pylori infection and CRC, colorectal polyps, and IBD in Indonesian tertiary Hospital.Method: We retrospectively collected data from patients referred to Dr. Cipto Mangunkusumo General National Hospital from 2010 to 2021 with a complete H. pylori test from electronic medical records. We performed a chi-square analysis and logistic regression with a significant p-value of 0.05.Results: Three hundred and fourteen patients were enrolled. Overall, the prevalence of H. pylori infection in organic bowel disease was 61.7% (n = 194), with 9.9% (n = 31) of them having CRC, 20.3% having colorectal polyps (n = 64), and 31.5% (n = 99) having IBD. A proven association between H. pylori infection and IBD was observed (RR = 0.36; 95% CI: 0.18‒0.70; p = 0.000). However, no significant association was found between H. pylori infection and CRC (RR = 0.60; 95% CI: 0.22–1.66; p = 0.31) and colon polyps (RR = 0.59; 95% CI: 0.30–1.15; p = 0.10).Conclusion: Our study suggested an association between H. pylori infection and IBD patients. However, an insignificant association was observed between H. pylori infection, CRC, and colorectal polyps. Keywords: Helicobacter pylori, inflammatory bowel disease, colorectal cancer, colorectal polyps